PENGEMBANGAN MEDIA KOMIK BERBASIS MASALAH UNTUK PENINGKATAN HASIL BELAJAR IPS SISWA SEKOLAH DASAR - Freddy Widya Ariesta; Erlina Novi Kusumayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2018)
Based on the results of the analysis of the needs in elementary school at Kalimacan Sragen regency, it is found that the learning result of the students is still low, the learning media used has not cultivated the students' learning interest and the presentation of the less interesting IPS learning materials. This type of research is the Research and Development (R&D) by Borg & Gall. Product validation test conducted by a team of experts or an expert assessment, practicality test conducted by questionnaire response after learning of students and teachers, as well as the effectiveness of the test conducted pre-exsperimental design with one group pretest posttest study. The results of this development research that is produced product of comic based media problem that